Greater China and Japan : prospects for an economic partnership in East Asia - Taylor, Robert, 1941- (Sheffield Centre for Japanese Studies/Routledge series., 1996)
In this compact and student-friendly textbook, Robert Taylor explores the ambiguous relationship between the two regions, and explains why its development will be so crucial in the twenty-first century.